Assessment of metal and metalloid contamination in the waters and stream sediments around the abandoned uranium mine area from Mortórios, central Portugal - Neiva, A. M. R. (2019)
In the abandoned Mortórios uranium mine area there are quartz veins containing wolframite and sulphides and basic rock dykes with torbernite and autunite cutting a porphyritic granite. The basic rock dykes were exploited and produced about 27 tonnes of U3O8, from 1982 to 1988. There are an open pit lake and nine dumps. Surface water and groundwater are contaminated in U, As, Cd, Cr, Cu, Fe, Mn, Ni and Pb. Stream sediments are contaminated in U, As, Th and W, which are adsorbed by smectite, kaolinite and iron- and aluminium- oxy-hydroxides. The maximum U concentrations are of 1268 ug/L in the open pit lake, 100 g/L in surface water, 103 ug/L in groundwater and 81.5 mg/kg in stream sediments all downstream of the open pit lake and dumps. Further downstream the U concentration in water decreases, due to the high mobility of U (VI), but the U concentration in stream sediments increases. Calcium uranyl carbonate dominates in the open pit lake, but uranyl carbonate complexes dominate in surface water and groundwater. The maximum As concentrations are 56.0 g/L in the open pit lake, 63.4 g/L in the surface water and 66.7 g/L in the groundwater, both downstream of the open pit lake and dumps. The arsenic occurs as As (V). The Mortórios area is compared with two other areas exploited from open pits, all located in the uranium-bearing Beira area of central Portugal. Vale de Abrutiga produced 90 tonnes of U3O8 between 1982 and 1989 and Mondego Sul produced 75 tonnes of U3O8 from 1987 to 1991. The two mines consist of quartz veins containing sulphides, saleeite and meta-saleeite at Vale de Abrutiga and with sulphides, autunite, torbernite, meta-uranocircite and meta-saleeite at Mondego Sul cutting the Schist-graywacke complex. The mine area of Vale de Abrutiga with the highest exploitation of U2O3 has strongly acidic to slight alkaline water, which is the most contaminated. Mortórios with the lowest exploitation presents a higher contamination of slightly acidic to alkaline water than that of acidic to alkaline water from Mondego Sul, but the former has As (V), whereas the latter has As (III), which is toxic. The stream sediments from Mortórios present the lowest contamination, except for Th that has a higher median value than that from Vale de Abrutiga. Stream sediments from Mondego Sul have higher U, Th, Pb and lower Co, Cr, Cu and Zn median values than those of Vale de Abrutiga.